Impacto da ressonância magnética pré-operatória nas pacientes com câncer de mama inicial candidatas à cirurgia oncoplástica - Anselmi, Karina Furlan (2015)
Aims: To evaluate pre-operative MR impact on patients with primary breast cancer eligible to oncoplastic surgery (OP); to compare MR results to those of mammography, US and anatomy-pathologic; to evaluate the impact of MR findings when changing the approach for mammography or in the improvement of surgical planning of patients eligible to OP; to evaluate the rate of positive margins and reoperation in this group of patients; and to evaluate patients undergoing mastectomy due to MR findings. Methods: Sixty (60) patients with primary breast cancer diagnosed through clinical, radiological (mammography and US), and anatomy-pathologic exam were prospectively studied. Subsequently, they underwent pre-operative MR exam for surgical planning. Results: From the 60 patients that underwent pre-operative MR, 29 (48.3%) had additional lesions detected. Among the additional lesions detected through MR, 16 (55%) were multifocal, 1 (3.4%) were multicentric, 5 (17%) were situated in the contralateral breast and 9 (31%) presented tumor size larger than 10mm in the MR when compared to the mammographic exam results and US results. MR was the imaging exam more closely associated with the tumor size obtained in the anatomo-pathologic exam when compared to mammography, US, and combined mammography and US, with p=0.033, p<0.001 and p=0.014, respectively. From the population studied that had additional lesions in the MR suspected of malignancy, 41% of the patients had their choice of approach changed and 58% of the patients had a better surgical planning using OP techniques and keeping the conservative approach. From the 60 patients that underwent MR, 12 (20%) underwent mastectomy and the choice for this procedure was due to the fact that 10 (83%) were multifocal, 1 (8.3%) was multicentric and 3 (25%) had cancer in the contralateral breast detected through MR. Among the 12 mastectomies performed, 83% were chosen due to the disproportional relation between the breast size and the tumor size, in addition to the presence of multifocality, and/or multicentricity as well as positive family history. The rates of positive margins were 5% in the total population studied and 3.4% in the patients that had additional lesion detected through MR. Conclusion: When MR is performed by physicians that are well-trained in pre-operative planning, when it is well-interpreted by the surgeon and it is associated with oncoplastic techniques, it provides better oncologic and aesthetic results to patients.